(untitled) (Mustansiria Dental Journal, 2018)
Background: From the ancient Greek (epilepsia). Seizure is common and diverse set of chronic neurological disorders characterized by seizures. Patients and Methods: The sample population comprised 10 epilepsy patients and 10 persons with no history of systemic disease, oral manifestation was recorded as well as saliva samples were taken. The IL-6, alkaline phosphatase and total salivary proteins had been measured. Results: The most frequent oral manifestation was gingival hyperplasia 85.7%, and dry mouth 75%, increased level of IL-6 and total salivary proteins in epilepsy patients receiving treatment, when comparing the level of alkaline phosphatase, slightly decreased in study group, with no statistical significance. Conclusion: In addition to the systemic effects of antiepileptic medication, and oral effects, including saliva composition and oral manifestation was recorded also. Therefore epileptic patients are at an increased risk of developing dry mouth, gingival hyperplasia, and alteration in saliva composition compared with health subjects. .